Effects of adding betaine on laying performance and contents of serum yolk precursors VLDL and VTG in laying hen - LU Jian-jun; ZOU Xiao-ting (浙江大学学报. 农业与生命科学版)
Eight hundred ISA laying hens of 20 weeks of age were tested to investigate the effects of betaine on contents of serum yolk precursors VLDL (very low-density lipoprotein) and VTG (vitellogenin) for 350 days. Laying hens were randomly allotted to four groups with four replicates each. The groups were fed a corn-soybean basal diet, supplemented with 0, 400, 600, 800 mg·kg-1 betaine. It indicated that addition of 600 mg·kg-1 betaine significantly improved egg production by 8.67% (P< 0.05) compared with control. Supplementation of 600 mg·kg-1 betaine increased concentration of VLDL by 34.61% (P<0.05) and 53.41% (P<0.03); VTG by 33.74% (P<0.01) and 39.14% (P<0.01), decreased activity of LPL in abdominal fat by 31.0% (P<0.01) and 44.83% (P<0.01) in 50 and 70-week old laying hens respectively. It indicates that the contents of serum yolk precursors VLDL and VTG were significantly affected by betaine in laying hen.